Desenvolvimento de uma torre automatizada para o resfriamento de água - Ferreira, Cleverson Krul (2014)
The present work refers to the development and assembly of an academic bench, which represents a closed loop system that simulates an automated water cooling tower. It presents bibliographical survey for theoretical-conceptual basis, which consists of the operating principle of the devices used, like electric motors, sensors and actuators, frequency inverters, programmable logic controller and supervisory system. The programmable logic controller and inverters programming manages the automated control system and the supervisory system modeling of the human- machine interface, has the priority of easy to use. The result was a prototype of an academic bench that monitors and automatically controls the water temperature set by the user.